ANALISIS RESIKO USAHA, PEMASARAN, DAN PENGARUH BIAYA PRODUKSI TERHADAP BESAR PENDAPATAN PENGUSAHA JENANG KETAN DI DESA COKROKEMBANG KECAMATAN NGADIROJO, PACITAN - administrator, administrator; inim, Sergiani Oktaviana; Humaidi, Faisol (Jurnal Agribisnis Wijaya Putra Surabaya, 2023)
This study aims to analyze the effect of production costs on the income of sticky ricejenang entrepreneurs, to determine the profit, business risk, and business efficiency ofsticky rice jenang at household level, and to analyze the marketing of sticky rice jenang inNgadirojo District, Pacitan Regency. This research uses descriptive analytical method.The determination of the research area was carried out purposively, namely inCokrokembang Village, Ngadirojo District, Pacitan Regency. The analytical method usedis to use multiple linear regression analysis. From the results of the research analysis, itcan be seen that the production costs that affect the income of the jenang entrepreneursmore are glutinous rice, the average profit earned by the glutinous jenang entrepreneursin a month is Rp. 8,192,063. The sticky rice industry has an efficiency value of 1.77.Glutinous jenang business has a low business risk because the standard deviation of theglutinous jenang business is Rp. 1,611,549. The magnitude of the coefficient value is 0.36.In other words, the jenang business can generate profits. Glutinous jenang is marketed inPacitan itself and outside the city such as: Milir market, Dalopo market, Madiun market,Purwantoro, Ngawi, Magetan and Trenggalek. There are three marketing channels forsticky rice, including producers - consumers, producers - retailers - consumers andproducers - agents - retailers - consumers